Design & fabrication of multipurpose household drying cloth and canopy / Muhammad Danial Zikri Abdul Jami and Zeno Michael - Abdul Jami, Muhammad Danial Zikri; Michael, Zeno (School of Mechanical Engineering, 2022)
Air Drying Cloth is the process of leaving cloth out in the open area so that the liquid in it evaporates as a response to the environment surrounding it. Air-drying eliminates static cling on fabrics and requires less energy, which saves money and has a lower environmental effect. In this project, a multipurpose household drying rack prototype was designed using Solidworks software and the concept was designed based on the product improvement of the existing product in the market. The selection of materials was considered in terms of their quality and price. This prototype includes a PVC fabric to protect the wet clothes from bad weather. Product analysis was done to identify the required maximum load of the rods that can hold before it fails. The fabrication process includes measuring, cutting, grinding, milling, drilling, and finishing process. This product has multi- functionality, can save space and is equipped with PVC Vinyl Fabric protecting the wet clothes from rain. The prototype can only hold a limited number of loads, does not have any motor or sensor and the movement of this prototype is also limited. These results show that although this prototype has some limitations and has to be manually operated, this project objective still can be achieved